Expectativas de la familia indígena frente a la educación :análisis de caso en la comunidad de pesillo, cantón Cayambe. - Vásconez Paredes, Carlos Dario (2017)
This research addresses the expectation of the indigenous family about education, for this we have made an approach from different points of view, such as: cultural, social, economic and organizational aspects. Also, the research is conceived in the community being the indigenous family the interest group, however, the educational community also has to be a very important actor for the development of the study. All this in order to understand how the family affects or not in the decision making of their sons and daughters at the time of graduation from high school and opt either for a higher education or for the job that can be found in or outside the community. Moreover, we will analyze if there is still a struggle to claim the rights of the indigenous family and preserve historical legacy or not. The study’s approach is qualitative, so the methodology to be used is summarized in three moments; In the first moment a territorial approach will be held in the community of Pesillo; In a second moment the Unidad Educativa del Milenio will be the axis of approach; And in a third moment we will work with the families, where we will apply techniques such as interview and participant and non-participant observation in order to collect data that contribute to our research topic.